Effectiveness of a protocolized nursing intervention on the treatment of the urinary incontinence in women from the province of Avila - Mª Teresa Martín Sánchez; Montaña Domínguez Aparicio; Loris George Khanouf Jalil; José Ignacio Isusquiza Carro; María Martínez Martín (Fundación para el Desarrollo de la Enfermería, 2008)
The current sensibilitation based on the gender differences carry out by the National Health System has showed several healthy problems that are mostly suffered from women and that need a proper attention. One of these problems is urinary incontinence, which is suffer from a huge percentage of women and it also affect and modify their normal habits or life. This necessity was detected some years ago, at the Hospital of Avila, Nuestra Señora de Sonsoles, thus, a urinary incontinence nursery's office was created in order to increase the women's self-care. Among the care plan developed there was a protocolized nursing intervention which consist on an improve modification of the Kegel exercises known as TERMAR method.A clinical trial was designed whose aim was to evaluate the benefits of the application of the integral and protocolized nursing intervention on women who suffer from urinary incontinence. To evaluate and measure this benefits several validated questionnaires will be used, such as the ICIQ-SF that measures the urinary incontinence symptoms severity, the King Health Questionnaire and the I-QOL, that determinate the repercussion on the daily life activities. We will besides use an electromiogram in order to determinate the strength of the pelvic floor musculature before and after the intervention.